PUBLIC DEBT AND ECONOMIC GROWTH : THE EMPIRICAL RESULT OF THAILAND - Tangkanjanapas, Passarapa; Thamma-Apiroam, Rewat; Dheera-aumpon, Siwapong (RMUTT Global Business and Economics Review, 2020)
This paper aims to study the effect of public debt to economic growth in Thailand using Two Stage Least Square estimators (2SLS). This study uses of time series quarterly data from 1998 to 2017. The regression results conclude that the relationship between public debt to GDP ratio and economic growth is non-linear and negative. The relationship between public to GDP ratio and economic growth is positive. The relationship between public to the square of GDP ratio and economic growth is negative. The highest turning point is at 48 Percent an inverted U-shaped. If debt exceeds this point, the relationship between GDP growth and public debt will change from positive to negative relationship.